Implementrasi Model Evaluasi CIPP (Context, Input, Process, Product) pada Pelaksanaan Program Pembangunan Pabrik di PT Garam - Khoirul Hidayat; Anang Siswanto (Journal of Energy, Materials, & Manufacturing Technology, 2023)
PT Garam has a construction capacity of 10 tph, but currently, of the 4 packaging machine lines that are running, only 1 machine line is running. This is a challenge for PT Garam to use the utilization of the 10 tph capacity design. Currently, the factory only has a utilization rate of 47% and an effective utilization rate of only 15.98%. With this research, it will be obtained related to what factors influence the building capacity of 10 tph not being utilized properly. To find out these factors, a CIPP (Context, Input, Process, Product) evaluation was carried out. Using this CIPP evaluation can improve a program and make a decision. Context evaluation has a suitability level of 71.11% because of the 4 machine lines only 1 machine is utilized. The input evaluation has a conformity level of 65.33% because the fine packaged product does not yet have a packaging distribution permit. Process evaluation has a suitability level of 53.33% because the level of machine damage that often occurs results in low utilization. Product evaluation has a conformity level of 74.44% because the grain of the rough product packaging does not match the specifications. Overall the suitability of the CIPP evaluation has a conformity of 66.06%, of this figure the factory is still in the criteria according to the development design.